Lange and his 1938-contribution An early Keynesian? - Finn Olesen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2006)
In February 1936 John Maynard Keynes gave birth to modern macroeconomics when he published The General Theory of Employment, Interest and Money. In some ways Oskar Lange was seemly also very critical of mainstream neoclassi-cal thinking although known as a working marginalist for the greater part of his life. In this note we try to identify what Lange might have had so say of Keynesian nature especially in an important contribution from 1938. I would like to thank Danuta Tomczak, Oestfold University College Remmen, Halden, Norway, and Heine Ruppert, Department of Environmental and Busi-ness Economics, for comments to an earlier draft of this paper.
Keywords: 330; Ökonomen; Keynesianismus; Dogmengeschichte; Polen